(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper mainly concerns environmental degradation in the past few decades. Overpopulation and the industrialization of society are the main causes of the exploitation of natural resources. Consequently, people are confronting the imbalances of the ecosystem in various aspects. Human-caused turmoil such as deforestation, the large amount of plastic production, pollution, and all other disasters disrupt the entire ecosystem. However, the ecological imbalances completely ruin the later generations’ living conditions as well. The overconsumption of natural resources would absolutely break the biocycle. Global warming plays a crucial role in the biosphere. The constant change in weather patterns is a consequence of greenhouse gas emissions. Comprehensively, the world is losing its basic natural substances. "Warned", "Awareness about Our Environment" and "The Brink" are poems by Sylvia Stults, an American writer who insists on the importance of environmental preservation in the future. Moreover, she envisions the climate crisis in her poems.